2013
DOI: 10.1002/ep.11794
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of activated carbon from Kraft lignin via KOH activation

Abstract: Kraft lignin (KL), which is largely obtained from Kraft pulping process, is typically utilized to generate steam, electricity, and heat. The huge amount of KL can also be utilized for various purposes such as producing biofuels, chemicals, and materials. In this work, industrial waste KL was used to prepare activated carbons (ACs) with high surface area and large pore volume via KOH activation method. The effects of pretreatment methods of KL, activation methods, and activation conditions on the pore structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…One drawback of lignin is the low carbon yield of only around 20-40% depending on the carbonization temperature [92]. [103].…”
Section: Precursors For Electrospinningmentioning
confidence: 99%
“…One drawback of lignin is the low carbon yield of only around 20-40% depending on the carbonization temperature [92]. [103].…”
Section: Precursors For Electrospinningmentioning
confidence: 99%
“…[33] Aftercarbonization of lignin,w es ee al arge mass loss (64mass%)c ausedb y thed ecomposition of theo xygeng roupsa th ight emperatures. [34,35] Thec arbonc ontent of LC increasest o8 4mass% and to approximately9 0mass% aftera ctivation( LK),w hereas the hydrogen ando xygenc ontents decrease.T he totaly ield of LK( % 21 mass %) is comparable to that of othera ctivated carbons derivedf roml igninb yu sing different activation techniques and pore-structure development( Y T = 13-35mass%). [36] Thermogravimetric analysisc oupled with mass spectrometry (TGA-MS)w as performed under an inert gas atmosphere (argon) to evaluate the surfaceg roups presenti nL Ka nd AC.…”
Section: Materials Characterizationmentioning
confidence: 99%
“…Li et al [18] stated that KOH activation of carbon-rich kraft lignin produces activated carbon with the superior surface area of 2763 m 2 /g. Muniandy et al [12] also showed that rice husk with 27% carbon content ends up with activated carbon with a similar surface area of 2696 m 2 /g.…”
mentioning
confidence: 99%